2007
DOI: 10.1080/00048670701579074
|View full text |Cite
|
Sign up to set email alerts
|

Future of God in Recovery from Drug Addiction

Abstract: The purpose of the present paper was to explore the concept and experience of God in relation to recovery from drug addiction from a scientific perspective. Examination of a diverse literature was undertaken, including five key threads: the universality of the experience of God; the induction of spiritual experiences of God through hallucinogenic drugs; the nature of drug addiction from an evolutionary neurobiological perspective; the 12 Step movement as the prototype for the place of God in recovery from drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…For example, spirituality decreased substance use among heroin-dependent individuals (Conner, Anglin, Annon, & Longshore, 2008), was associated with fewer alcohol relapses in alcohol-dependent persons (Sterling et al, 2007) and contributed to long-term recovery from cocaine dependence (Flynn, Joe, Broome, Simpson, & Brown, 2003). Religious beliefs embedded in Alcoholics Anonymous and Narcotics Anonymous, specifically Biblical scriptures that encourage individuals to surrender to a higher power (i.e., God) and to use religious practices (e.g., prayer, meditation) to become mindful and aware of self and others (Timmons, 2010), have also been influential in recovery from alcoholism (Bowden, 1998) and drug addiction (Sellman, Baker, Adamson, & Geering, 2007). In addition, a persistent reliance on faith has been shown to reduce substance use over time, suggesting that adherence to a stable belief system can minimize doubts and uncertainties in the recovery process and help to maintain pro-social attitudes and behaviors (Duvall, Staton-Tindall, Oser, & Leukeld, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, spirituality decreased substance use among heroin-dependent individuals (Conner, Anglin, Annon, & Longshore, 2008), was associated with fewer alcohol relapses in alcohol-dependent persons (Sterling et al, 2007) and contributed to long-term recovery from cocaine dependence (Flynn, Joe, Broome, Simpson, & Brown, 2003). Religious beliefs embedded in Alcoholics Anonymous and Narcotics Anonymous, specifically Biblical scriptures that encourage individuals to surrender to a higher power (i.e., God) and to use religious practices (e.g., prayer, meditation) to become mindful and aware of self and others (Timmons, 2010), have also been influential in recovery from alcoholism (Bowden, 1998) and drug addiction (Sellman, Baker, Adamson, & Geering, 2007). In addition, a persistent reliance on faith has been shown to reduce substance use over time, suggesting that adherence to a stable belief system can minimize doubts and uncertainties in the recovery process and help to maintain pro-social attitudes and behaviors (Duvall, Staton-Tindall, Oser, & Leukeld, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…becomes increasingly compulsive [1–4]. Although not understood fully at a neurobiological level, the normal flexibility of human behaviour guided by neocortical ‘higher power’[5] appears to become increasingly eroded towards a dehumanized state of compulsive behaviour, the ‘sticky’ repertoire of habitual behaviour that constitutes the addictive life‐style, mediated by a ‘compulsive circuit’ (nucleus accumbens, ventral pallidum, thalamus and orbitofrontal cortex) [6]. Thirty years ago the diagnostic concept of addiction (dependence) in the DSM‐III [7] was focused around neuroadaptation to drugs—evidence of acquired tolerance and/or withdrawal symptoms.…”
Section: Addiction Is Fundamentally About Compulsive Behaviourmentioning
confidence: 99%
“…Recovery from addiction involves a re‐orientation from self‐deception to the pursuit of higher ideals [5]. New meaning and hope in life is required, a spiritual experience, which for some is best described as ‘finding God’.…”
Section: Epiphanies Are Hard To Manufacturementioning
confidence: 99%
“…Recent studies have reported that of addiction sufferers who stop using drugs, approximately 60–80% resume drug usage (Cornelius, ; Ministry of Justice in Taiwan, ; United Nations Office on Drugs and Crime, ). Hence, abstaining from substance use is one of the great challenges of recovery from drug addiction, as drug addiction leads to physical, mental, and spiritual suffering for the users, their families, and society in general (Gray, ; Sellman, Baker, Adamson, & Geering, ). Individuals who use and abuse substances tend to become more dependent chronic users, which results in not only physical, psychiatric, and medical comorbidities, but also their stigmatization and marginalization by all segments of society (Cami & Farré, ; United Nations Office on Drugs and Crime, ).…”
mentioning
confidence: 99%
“…The addiction to substances has been defined as a behavioral disorder mediated by neurobiological changes in the brain (National Institute on Drug Abuse, ; Sellman et al., ). It has also been described as the manner in which the behaviors associated with drug abuse appear to become increasingly driven by forces outside of the person's conscious control, such as compulsive drug seeking and drug use (Robinson & Berridge, ; Sellman et al., ).…”
mentioning
confidence: 99%